A 10-Year Study on Larynx Preservation Compared With Surgical Resection in Patients With Locally Advanced Laryngeal and Hypopharyngeal Cancers - Su, Xuan; He, Hui-Chan; Ye, Zu-Lu; Zhou, Da-Lei; Liu, Qing; Yang, Xin-Hua; Long, Ya-Kang; Tang, Tao; Ma, Jiang-Jun; Xu, Bo-Heng; Chen, Wei-Chao; He, Cai-Yun; et al. (Frontiers in Oncology, 2020)
Background: The effectiveness of larynx preservation strategy in managing patients with locally advanced cancer is seldom reported. This study assessed the clinical outcomes of patients with locally advanced laryngeal and hypopharyngeal cancers treated with larynx preservation and determined the optimal larynx preservation procedure. Methods: Data of 1494 patients treated with total laryngectomy or larynx preservation between 2006 and 2014 were retrieved from the data base of Sun-Yat Sen University Cancer Center in Guangzhou, China, and 366 eligible patients were selected for final analysis. During larynx preservation treatment, the efficacy assessment of clinical tumor response was applied after two cycles of induction chemotherapy. A complete or partial response of the primary tumor and no sign of progression in the neck, a third course of chemotherapy was given, followed by radiotherapy. Results: Patients who received larynx preservation showed no statistical difference for 3-, 5- and 10-year PFS and OS compared with patients treated with laryngectomy. With respect to T stage, the larynx preservation group showed a better OS in T2-stage disease (P = 0.029) but poorer PFS (P = 0.004) in T3-stage disease compared with the surgery group in Univariate analysis. T3-stage disease still had poorer PFS in multivariable analysis. With larynx preservation intent, induction chemotherapy followed by radiotherapy showed no advantage in the control of distant metastasis and survival compared with concurrent chemoradiotherapy. When the factor of efficacy assessment was performed during administration of the induction chemotherapy was considered, the subpopulations who received efficacy assessment exhibited significantly longer PFS and OS compared with those without efficacy assessment. Conclusions: This is the largest sample size study on larynx preservation treatment for laryngeal and hypopharyngeal cancers in China. Our results indicated that larynx preservation treatments did not jeopardize the survival of patients with advanced but resectable laryngeal or hypopharynx cancers. Efficacy assessment should be emphasized in induction chemotherapy.